Tunggu Tubang: Marginalisasi Perempuan Semende - Arifin, Zainal; Delfi, Maskota; Pujiraharjo, Sidarta (Sunan Kalijaga State Islamic University & The Asia Foundation, 2017)
Semende ataupun komunitas Semendo adalah sebuah kelompok etnik yang tinggal di daerah pegunungan Sumatra Selatan. Sebuah aspek penting dari kultur kehidupan mereka adalah tunggu tubang. Menurut tradisi, kekayaan keluarga yang terdiri dari rumah keluarga dan lahan pertanian, akan diserahkan kepada anak perempuan tertua dalam setiap generasi. Artikel ini bertujuan untuk menjelaskan tradisi tunggu tubang sebagai identitas yang unik yang membedakan komunitas Semende dengan komunitas lain. Disamping untuk menjaga keberlangsungan komunitas, tunggu tubang juga sebagai alat legitimasi untuk kontrol kekuasaan gender oleh laki-laki di masyarakat. Tunggu Tubang sebagai alat legitimasi laki-laki terbukti dari penempatan perempuan â€œatas nama adatâ€ tampaknya memiliki kekuatan. Maka, komunitas Semende dikenal menggunakan sistem matrilineal. Bagaimanapun, tunggu tubang menguatkan posisi laki-laki yang memposisikan dirinya sebagai meraje, yang â€œatas bama adatâ€ juga dianggap berhak untukk mengontrol (seringkali sewenang-wenang) keberlanjutan tunggu tubang.[The Semende or also known as Semendo communities are a distinctive ethnic group residing in the mountainous areas of South Sumatra Province. An important aspect of their cultural life is known as tunggu tubang. According to tradition the familyâ€™s property, which consist of family house and agricultural fields, are passed on to the eldest daughter in each generation. This article attempts to explain the position of tunggu tubang as a unique identity differentiator of the Semende communities in contrast with other communities. Besides a means to protect the communityâ€™s survival, tunggu tubang has developed at the same time as a tool of legitimacy of political gender power control by males in the community. Tunggu tubang as a tool of legitimacy of men is evident from the placement of women â€œin the name of customâ€ seem to have power, so the community is often legitimized Semende as matrilineal. However, tunggu tubang is strengthening the position of the man who positioned himself as meraje that â€œin the name of customâ€ is also considered to be entitled to control (often arbitrarily) tunggu tubang sustainability.]